(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: In the last few decades, there has been exponential growth in the field of herbal remedies. Pharmacopoeial preparations such as avleha (semisolid), swarasa (expressed juice), kalka (mass), him (cold infusion) and phanta (hot infusion), kwatha (decoction), and churna (powder) form the backbone of Ayurvedic formulations. Newer guidelines for standardization, manufacture, and quality control, and scientifically rigorous research will be necessary for traditional treatments. This traditional knowledge can serve as a powerful search engine that will greatly facilitate drug discovery. Aim: The aim of this study is to standardize Chanaka Yoga in Kwath churna form. The powder form makes this traditional drug more stable for long-term storage and hence, easier to preserve. Materials and Methods: Chanaka Yoga Kwath churna is an Ayurvedic formulation containing Chanaka (Cicer aritinum) as one of its chief ingredients. The basic preparation of this drug is a Kwath churna. We checked the microbial load and nutrient values (using International Standard IS and Association of Official Analytical Chemists methods). Results: The powdered form of Chanaka Yoga Kwath churna yielded a weight loss of approximately 2.5% of the total weight of ingredients. The quantity of total fiber of Churna was found higher. Conclusion: Chanaka Yoga Kwath churna may be a good therapeutic and dietary medicine for Diabetic patients, which may be easily prepared at home.